Development and Validation of an ELT Game-based Material Development Scale - Abbasi Aram, Ali; Khany, Reza (Assessment and Practice in Educational Sciences, 2025)
With the expansion of educational technologies, the development of aligned online materials is of paramount significance. Despite this importance, little effort, if any, has been made to yield standard frameworks within which Ed-tech assisted materials could be developed and evaluated. Therefore, this study aims to develop and validate an ELT game-based material development scale. To this end, based on a systematic literature review and analysis of game- based material development models, a three-factor model comprising three main constructs and 24 sub-constructs was developed. This model then informed the creation of an initial item pool of 88 items. After expert evaluation, the original item pool was reduced to a final selection of 70 items. Through AMOS (version 26), confirmatory factor analysis was run to test the conceptual model of the study. The study was piloted by 340 participants. The developed scale can be used by ELT practitioners, researchers, material developers, and teachers in the field